PENGARUH KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Muhyarsyah . (Jurnal Riset Akuntansi dan Bisnis, 2007)
This Study investigated the influences of debt to the firm value.Furthermore, this study investigated the effect of the insider ownership, firm sizeand profitability to the firm value too. Using purposive sampling, this studyinvolves the 95 sample size and those data have met normality test. The analysis ofdata use the structural equation modeling (SEM). The Result shows that debt policyhad positif effect and not significant to the firm value. Insider ownership, firm sizeand profitability had positive and significant effect to firm value.